Implementasi Moderasi Beragama di Madrasah Aliyah Tahdzibun Nufus Jakarta dalam Terbentuknya Nilai-Nilai Moderasi Beragama - Akmal Nurullah; Bina Prima Panggayuh; Sapiudin Shidiq (MA'ALIM: Jurnal Pendidikan Islam, 2022)
Religious moderation is a very important activity carried out by Indonesian people who have different beliefs and religious backgrounds. Religious leaders who are supported by the government are trying to prevent and anticipate radical and intolerance events in Indonesia. One of them is by holding interfaith religious moderation. The concept of moderate Islam is a religious perspective that is very relevant in the context of diversity in Indonesia. As a form of strengthening and strengthening the role of Madrasah Aliyah in countering radicalism and extremism, it is necessary to internalize religious moderation in the Madrasah Aliyah curriculum. Which aims to mediate these two extreme poles, by emphasizing the importance of substantively internalizing religious teachings on the one hand, and contextualizing religious texts on the other. To examine these problems, researchers used qualitative research methods. This type of research includes case study research, which is a qualitative research that seeks to find meaning, investigate processes, and gain deep understanding and understanding of individuals, groups, or situations. In analyzing the data, the researcher took the interactive model as the presentation. Activities in data analysis include data reduction, data presentation as well as drawing conclusions and, verification. The results of the study of religious moderation that were instilled in the students of MA Tahdzibun Nufus Jakarta were not in a formal atmosphere, inserted in every lesson. The factors that influence the religious moderation spirit of the students of MA Tahdzibun Nufus Jakarta are young people who think more modern according to their times, are involved in activities directly. The form of moderation practiced by the students of MA Tahdzibun Nufus Jakarta is giving each other advice between students, this practice raises concern among friends.